Personality, interpersonal identification and agent’s performance in Multilevel Marketing Industry (MLM): preliminary - Shaierah Gulabdin; Toh, Pei Sung; Stephen Laison Sondoh Jr. (Human Resource Management Academic Research Society (www.hrmars.com), 2020)
Purpose – This paper aims to explore the influence of personality traits on agent’s performance in MLM industry based in Malaysia, taking into consideration the mediating role of interpersonal identification. Design/methodology/approach – The Big Five Factors (BFF) of personality traits was used in this paper. Previous research and literature is reviewed to establish current practices and point to gaps to be filled to meet the market needs. This paper proposed a framework with interpersonal identification as a mediating factor of agent’s performance. Findings – The Multilevel Marketing (MLM) industry faces challenges in attracting and maintaining agents in their roles. The big five factors alone cannot effectively explain agents. Agent’s interpersonal identification can play a significant mediating role in the big five-factor framework in predicting agent’s performance. It is important for industry and academia to work collaboratively to educate the general public on the rewards and benefits of working in the MLM industry. Practical implications – Adopting strategies described in this study may contribute to social change by increasing the success rate among multilevel marketers, thus reducing unemployment, and producing a positive effect on the economy. Originality/value – This paper adds value and contributes to the MLM industry and academia, as it represents current research and thought processes from both the academic community and the practitioners (sales managers, executives, supervisors, human resources managers). The proposed framework in this paper helps researcher by providing a tool for systematic evaluation and testing of real empirical situation of agent’s performance